THE COMPARISON OF READING COMPREHENSION IN DESCRIPTIVE TEXT INSTRUCTION USING CASE STUDY AND ANALYTICAL TEAM OF STUDENTS AT SENIOR HIGH SCHOOL OF STATE 1 KOTAGAJAH ACADEMIC YEAR 2012/2013 - Rosiana - -; Eva - Faliyanti (Premise: Journal of English Education and Applied Linguistics, 2013)
Reading comprehension in descriptive text is the ability students of understanding and interpreting information in a descriptive text correctly or get meaning from written descriptive text based on some aspects. Many techniques presented as a solution in reading comprehension they are Case Study technique and Analytical Team technique. The problem formulation in this research are; (1) Is there any significant difference between using Case Study and Analytical Team toward students’ reading comprehension in descriptive text instruction for the tenth grade students of SMAN 1 Kotagajah (2) Which one is more effective between using Case Study and Analytical Team toward students’ reading comprehension in descriptive text instruction for the tenth grade students of SMAN 1 Kotagajah. The objectives of this research are (1) To know whether there is significant difference between using Case Study and Analytical Team toward students’ reading comprehension in descriptive text instruction for the tenth grade students of SMAN 1 Kotagajah. (2) To find out which one is more effective between using Case Study and Analytical Team toward students’ reading comprehension in descriptive text instruction for the tenth grade students of SMAN 1 Kotagajah.In this research, the researcher uses an experimental design. The kind of design is True Experimental Control Group Pre-test and Post test. Experimental group is taught Case Study and control group taught Analytical Team technique. The population in this research is 694 students. The sample in this research is class X which consists of 2 classes 44 students and each class consist of 22 students are as experimental class and 22 as control class. The writer use cluster stratified random sampling to takes sample. From the accounting of students score on post test, is was gained that at the significant level of 0,01, the tratio is higher than ttable, that is 2,77 for tratio and 2,70 for ttable.The conclusion are; (1) There is significant difference between using Case Study and Analytical Team toward students’ reading comprehension in descriptive text instruction for the tenth grade students of SMAN 1 Kotagajah. (2) Case Study is more effective than Analytical Team toward students’ reading comprehension in descriptive text instruction for the tenth grade students of SMAN 1 Kotagajah. It means that Case Study effective to develop students’ reading comprehension